A Profile of the World's Young Developing Country International Migrants - McKenzie, David J. (2012)
Individual-level census and household survey data are used to present a rich profile of young developing country international migrants around the world. They are found to comprise a large share of the flow of migrants, particularly among migrants to other developing countries, with the age distribution of migrants peaking in the late teens or early twenties. Detailed data are presented on the age and sex composition of migrants, on whether young migrants move alone or with a parent or spouse, on their participation in schooling and work in the destination country, on the types of jobs they have, and on the incidence and age of return migration. The results suggest a high degree of commonality in the youth immigrant experience across a number of destination countries. Recent developing country young migrants tend to work in similar occupations and are more concentrated in these occupations than recent older migrants or young immigrants who arrived at an earlier age. Nevertheless, there is also considerable heterogeneity among young immigrants with respect to school attendance and work in their destination country. The potential of international migration for building human capital is significant but far from being fully used.